Health status of adults exposed to severe acute malnutrition during childhood in the Eastern Democratic Republic of the Congo: the Lwiro cohort study - Jonathan C Wells; Michèle Dramaix; Michel P Hermans; Ghislain Bisimwa; Christian Chiribagula; Samuel Makali; Gaylord Ngaboyeka; Christine Chimanuka; Corneille Lembebu; Rosine Bigirinama; Pacifique Mwene-Batu (BMJ Public Health, 2025)
Background While most studies of adults with a history of severe acute malnutrition (SAM) focused on survival and long-term non-communicable diseases, few studies have examined community health. The aim of this study was to compare the overall health status and its predictors between adults with a history of SAM and healthy controls in the context of Eastern Democratic Republic of the Congo using the WHO Disability Assessment Schedule (WHODAS).Methods We evaluated 257 adults in Eastern Democratic Republic of the Congo who were treated for SAM during childhood between 1988 and 2007. They were compared with 187 age-matched and sex-matched control adults living in the same community who had not been exposed to malnutrition as a child. The main outcome was the WHODAS summary score, measuring an individual’s health status in six domains of disability (household daily tasks, cognitive, mobility, self-care, social networks and social participation). A multivariable logistic regression model was used to identify the predictors of health status.Results The median age of the participants in both groups was 20 years. The median (P25–P75) WHODAS score in SAM+ participants was 25.0 (14.6–33.3), whereas it was 8.3 (4.2–14.6) in SAM− participants (p<0.001). In five of the six disability domains (except individual self-care), SAM+ participants had significantly higher scores (poorer health) than SAM− participants. Consequently, 63% of SAM+ participants had a higher level of dependency compared with 16.6% of SAM− participants. Finally, being SAM+ was predictive of a higher WHODAS score (OR 8.6, 95% CI 5.4 to 13.6, p=0.002). In the multivariable logistic regression model, occupation, socioeconomic status and use of social networks, introduced separately in addition to SAM, remained significant but had no confounding effect on the association between SAM and WHODAS score.Conclusion SAM during childhood has deleterious consequences on the state of health during adulthood. It is imperative to implement interventions to prevent and treat SAM during childhood to maximise adult population health.